CANVA-BASED INTERACTIVE MULTIMEDIA ON STUDENTS’ CRITICAL THINKING SKILLS AND MATHEMATICS SELF-EFFICACY - Yuliyanto, Aan; Utami, Candra Tri; Fujiarti, Ari; Andriyantono; Ramdani, Rizki (AULADUNA: Jurnal Pendidikan Dasar Islam, 2025)
The purpose of this study was to determine the outcomes of critical thinking skills and mathematical self-efficacy when using interactive multimedia with canva. This study used a quasi-experimental, unequal pretest-posttest control-group design. The study population was all fifth-grade elementary school students in West Java. The instruments in this study were tests, attitude scales, observations, and documentation. The results of the critical thinking ability test and the mathematical self-efficacy attitude scale were tested using descriptive and inferential statistics. The results showed that there was a difference in the outcomes of critical thinking skills in the experimental class, when canva-based interactive multimedia was applied, compared to the control class. The outcomes of mathematical self-efficacy also differed between the experimental class, which used canva-based interactive multimedia, and the control class. Thus, critical thinking skills and mathematical self-efficacy learned through canva-based interactive multimedia were significantly better than those learned through conventional instruction.